Implementation of Action to Control Hallucinations: Training to Rebuke Auditory Hallucinations in the Saraswati Room of dr. H. Marzoeki Mahdi Hospital, Bogor - Reni, Reni (STIKes RSPAD RSPAD Gatot Soebroto, 2023)
Hallucinations are mental disorders in which clients experience changes in sensory perception, feel false sensations in the form of sound, sight, taste, touch, or smell. Signs and symptoms of hallucinations include: talking, laughing and smiling to themselves, getting angry for no reason, covering their ears, covering their nose, and being afraid of something unclear. Ways to prevent hallucinations include managing stress by doing relaxation techniques such as meditation, avoiding triggers that cause stress, getting enough sleep, maintaining mental health, and avoiding mentally detrimental environments. The author's purpose in this scientific paper is to implement actions to control hallucinations: training to rebuke auditory hallucinations. This writing uses a descriptive case study method design that aims to create descriptions and descriptions of training to rebuke, data collection using interviews, observations, documentation, and demonstrations. The results obtained were after being carried out for three days from February 27, 2023 to February 29, 2023, at the third meeting it was found that when training to rebuke had a great effect on patients with auditory hallucinations because it could reduce the signs and symptoms experienced, so it can be concluded that training to rebuke is very effective in patients with auditory hallucinations. The conclusion is the application of actions to control hallucinations: training to rebuke can reduce the appearance of signs and symptoms of hallucinations, patients are very cooperative in participating in activities.